Ответы и объяснения

2013-02-05T18:07:17+04:00

-6 + z = 0                       (-3.8):x = 38                     2(x+3) = 12

Z = 6.                              x = -3.8:38                      2x + 6 = 12

                                       x = -0.1                           2x = 6

                                                                              x = 3

 

z/5 + 3 = -7                     8x - 12 = 3x + 8                0.8у+1.2=0.4у-2.8 

z/5 = -10                          5x = 20                            0.4y = -4 

z = -50                              x = 4                                y = -10